AKTIVITAS SITOTOKSIK SENYAWA Α-TERPINEOL PADA CELL LINE KANKER LEHER RAHIM (SEL HeLa) SEBAGAI SUMBER BELAJAR BIOLOGI MATERI POKOK BIOLOGI SEL - Rasuane Noor (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
α-terpineol is a compound of the class of terpenoid alcohols derived from natural materials, α-terpineol can be synthesized from α-pinene from turpentin content of extracts derived from the sap of pine trees (Pinus merkusii). α-terpineol has been reported as a natural compound that has potential as anticancer agent. Objectives of research: In general, to assess the activity of α- terpineol compounds against HeLa cells and the possible mechanism, whereas specifically assessing cytotoxic activity. Methods: This was a quasi-experimental study using post-test only with non-equivalent control group design. This study was conducted on HeLa cells by administering α-terpineol. Observations cytotoxic activity assay was performed using MTT assay method. Results: α -terpineol was cytotoxic against HeLa cells with IC50 of 12,46 μg/mL, therefore this compound was a potential anticancer Kata kunci : α-terpineol, sitotoksik, HeLa, kanker leher rahim